TRANSIENT OVERVOLTAGE ON 500 KV TRANSMISSION LINE PLAN IN SARAWAK USING POWER SYSTEM COMPUTER AIDED DESIGN - NUR IZZIANI, ROSLAN (Universiti Malaysia Sarawak (UNIMAS), 2018)
Transmission system is a crucial system in electrical power since the system transmit the electricity from power generation to consumer’s load. The power losses of the transmission line were rapidly changing from year to year at the rate of 3.85% in the year of 2013 to 5.792% in 2014. Losses in transmission system are most likely from power quality problems such as transients. Transients are the high unexpected increment in voltages or currents magnitudes. The peak values of both voltages and current are usually more than twice of that normal voltage and current amplitudes. The surges due to transients can vitally cause power system failure and breakdown of electrical equipment especially at the substations. There were few known transient overcurrent and overvoltage problems which are due to faults, lightning and line energizing. This project is mainly about simulating transients for 500 kV transmission system which use Sarawak as the case study location. Sarawak has main 275 kV Transmission line covering the whole Sarawak from Miri to Kuching known as Sarawak backbone, but due to lots of industries and human population increase in Sarawak, there is planned a 500 kV transmission as a backup if the power failure at the 275 kV transmission line. In Sarawak, the 500 kV was planned to be energized at 275 kV. But, in fact this project was for that transmission line to be operated at 500 kV hence, monitored the highest transient may occur. Overall, lightning and three phase faults of 1.0 s fault time duration cause biggest change in amplitude current of the line up to 9.06 pu and 9.27 pu. Highest lightning amplitude observed when lightning was been simulated at the receiving end of the line which is near to the Tada substation. Substations should be equipped with high performance electrical protection equipment since substation were linked to other transmission lines or consumers load and usually own equipment such as transformer that was costly and hard to maintain once broken.